Legal Protection and Criminal Implications of Mistreatment of Minors: Analysis Based on Child Protection Law Number 35 of 2014 - Azahra, Astrid Sulistya; Ulyana, Yaza Azzahara; Riyansyah, Ahmad (International Journal of Humanities, Law, and Politics, 2023)
This study discusses the abuse of minors and the legal implications and protections afforded to victims. Child maltreatment is an act of violence involving minors under the age prescribed by law, including physical, emotional, and sexual abuse. The Child Protection Law regulates cases of child abuse and provides a strong legal basis for protecting children's rights. The criminal implications of child maltreatment include various legal consequences imposed on perpetrators, such as imprisonment and fines. The main purpose of these criminal implications is to ensure justice for victims, prevent the repetition of similar crimes, and give an unequivocal message that child maltreatment is unacceptable. Protection of victims of child abuse covers a wide range of aspects, including victims' rights to feel safe, privacy, physical and psychological recovery, uninterrupted education, justice in due process, fair compensation, and effective protection from authorities. Parents also have an important role in providing protection to children who are victims. Cooperation from various parties, including the state, government, community, and family, as well as the implementation of strong laws, are expected to prevent cases of abuse of minors, ensure the protection and recovery of victims, and realize justice.